Bioestratigrafía del Pleistoceno en el río Arrecifes, Buenos Aires - Pasquali, Ricardo C. (1999)
In this papper a biostratigraphic interpretation for the río Arrecifes valley, Buenos Aires province, Argenline, is given. In reference to the problema tic recognilion of the "Lujanian"-"Bonaerian", the identily of the Stage/Age Bonaerian (middle-Iate Pleistocene) for the are a under study is conlirmed on the basis of the paleofaunc discovered.